Seminal fluid and sperm diluent affect sperm metabolism in an insect: Evidence from NAD(P)H and flavin adenine dinucleotide autofluorescence lifetime imaging - Massino, Christian; Wetzker, Cornelia; Balvin, Ondřej; Bartonicka, Tomáš; Kremenova, Jana; Sasinkova, Markéta; Otti, Oliver; Reinhardt, Klaus (Microscopy research and technique, 2022)
Sperm metabolism is fundamental to sperm motility and male fertility. Its measurement is still in its infancy, and recommendations do not exist as to whether or how to standardize laboratory procedures. Here, using the sperm of an insect, the common bedbug, Cimex lectularius, we demonstrate that standardization of sperm metabolism is required with respect to the artificial sperm storage medium and a natural medium, the seminal fluid. We used fluorescence lifetime imaging microscopy (FLIM) in combination with time-correlated single-photon counting (TCSPC) to quantify sperm metabolism based on the fluorescent properties of autofluorescent coenzymes, NAD(P)H and flavin adenine dinucleotide. Autofluorescence lifetimes (decay times) differ for the free and protein-bound state of the co-enzymes, and their relative contributions to the lifetime signal serve to characterize the metabolic state of cells. We found that artificial storage medium and seminal fluid separately, and additively, affected sperm metabolism. In a medium containing sugars and amino acids (Grace's Insect medium), sperm showed increased glycolysis compared with a commonly used storage medium, phosphate-buffered saline (PBS). Adding seminal fluid to the sperm additionally increased oxidative phosphorylation, likely reflecting increased energy production of sperm during activation. Our study provides a protocol to measure sperm metabolism independently from motility, stresses that protocol standardizations for sperm measurements should be implemented and, for the first time, demonstrates that seminal fluid alters sperm metabolism. Equivalent protocol standardizations should be imposed on metabolic investigations of human sperm samples.
Keywords: flavinadenindinukleotid; FLIRR; Flavin-Adenine Dinucleotide; Male; bedbug; Sperm Motility; Spermatozoa; mužské pohlaví; metabolic mapping; Bedbugs; Animals; FLIM; mikroskopie fluorescenční multifotonová; zvířata; motilita spermií; štěnice; spermie; Microscopy, Fluorescence, Multiphoton; NADP; Cimex lectularius; multiphoton microscopy; spermatozoa